DETERMINING OPTIMAL CAPACITY OF DISTRIBUTED GENERATION UNITS IN MULTIPLE ENERGY CONVERSION CENTERS CONSIDERING LOAD UNCERTAINTY USING ACO AND PSO ALGORITHMS - Rozveh, Rasoul Salehi; Kamarposhti, Mehrdad Ahmadi (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2018)
Capacity of Distribute Generation (DG) unit vary from several kilo watts to tens of Megawatts; it is used to generate electrical energy close to consumers. If these units are connected to the grid, the grid is affected in many aspects including reduction of losses of the network, improvement in voltage profile and increase in network reliability. Inappropriate placement of DG units increases losses, generation and transmission costs. Therefore, optimization methods are required for placement of these units in the grid; thus, number of DG units, installation location and their capacities should be determined such that grid loss is reduced as much as possible under grid constraints. In this project, Ant Colony Optimization and Particle Swarm Optimization algorithms are used to solve the problem. After extracting flowchart of this method for optimal placement of DG units, computer programs are formulated and implemented on a standard IEEE 33-bus radial grid and obtained results are compared; their advantages and disadvantages are suggested. Obtained results indicate voltage profile and reduce network losses.